THE DEVELOPMENT OF SUBJECT MODULE OF THE PRINCIPAL STRING INSTRUMENT (BEGINNER) AT THE MUSIC ARTS STUDY PROGRAM, FBS, UNESA - Vivi Ervina Dewi; Harpang Yudha Karyawanto; Dhani Kristiandri (FBS UNY, 2021)
This study program is under the Department of Art, Drama, Dance, and Music, Faculty of Languages and Arts, Universitas Negeri Surabaya. This program uses the Independent Learning Curriculum. A course on the principal string instrument (beginner) is featured in the third semester. However, there are still many issues with its execution. Due to the COVID-19 pandemic, students must study at home. Thus, this scenario affects students' capacities. As a result, this research will show the development and effectiveness of a subject module of the principal string instrument (beginner) at the Faculty of Languages and Arts, Universitas Negeri Surabaya. This study uses the ADDIE learning design model (Analysis-Design-Develop-Implement-Evaluate). Learning products research produces a learning module designed to help students improve their violin playing skills, especially in the principal string instrument (beginner). Developing the principal string instrument (beginner) learning module begins with a needs analysis based on observation, field studies, and literature. Each stage of product development involves analysis, design, development, implementation, and evaluation. The design results were assessed by material, language, and graphic experts and revised. After revisions, the product was tested on students of the music arts study program, Universitas Negeri Surabaya. The results are packaged as learning modules for music arts lecturers and students. The development research results show that using products in learning modules can improve violin playing skills. The t-test value of 0.000 indicates that the experimental and control groups differ significantly.Keywords: Development, Module, Learning, Violin.